Studi Eksperimen Pengaruh Bentuk Saluran Pada Corrugated Collector Terhadap Performa Pengering Tomat Tenaga Surya - Arrad Ghani Safitra; Lohdy Diana; Farida Gamar; Novita Astin; Diki Candra Kusuma; Rio Bagus Sasongko (P3M Politeknik Negeri Cilacap, 2026)
Solar Air Heaters (SAHs) are a strategic solution to mitigate post-harvest losses of horticultural commodities caused by inefficient conventional drying. This study aims to analyze the effect of serpentine absorber channel geometries integrated with Fresnel lenses on collector thermal performance and drying effectiveness. The experimental method involved testing three absorber channel cross-sections—triangular, rectangular, and trapezoidal—under outdoor conditions. The results indicate that the trapezoidal design offers superior thermal performance compared to other variations. The trapezoidal collector produced a maximum outlet air temperature of 88.5°C, a useful heat gain of 1,744.49 Watts, and a thermal efficiency of 50%. Application to tomato drying demonstrated that the system reduced drying time by half compared to open sun drying and significantly lowered product moisture content. This study concludes that integrating a trapezoidal absorber with a Fresnel lens effectively enhances the performance of active solar drying systems.